Observations of Channel Change from Constructed Wood Jams on a Forested Gravel‐Bed Stream. Issue 1 (16th December 2016) - Flannery, Joel; Stubblefield, Andrew; Fiori, Rocco; Shea, Conor
Abstract: Salmonids in the Pacific Northwest face a number of threats: habit degradation, loss of habitat, overharvest, competition from hatchery fish, dams, and climate change. Wood has been shown to play a key role in many aspects of stream habitat quality; however, it is in low supply in many Pacific Northwest streams because of wood removal and timber harvest practices in riparian zones. Wood placement for restoration has the potential to benefit salmonid populations. However, common applications often fall short of producing the physical changes necessary to achieve the objectives, such as the formation of deep pools and cover. This study evaluated the hypothesis that wood jams constructed with whole‐tree materials, high wood piece counts, and high wood volumes would be effective at creating instream geomorphic complexity, function, and aquatic habitat quality. Results were based on an evaluation of changes to surface sediment textures and channel morphology at eight constructed wood jams built with varying complexity, wood volumes, and whole‐tree materials, including large‐diameter trees with an attached rootwad, logs, and branches. We found that complex wood jams created statistically significant changes that include increasing percentage pool cover, increasing scour pool habitat, and sorting and metering gravel, resulting in an increase in the proportion of the stream bed composed of gravels appropriately sized for local species of spawning salmonids, increased habitat heterogeneity, and increased gradient and channel width. Received May 27, 2016; accepted September 1, 2016 Published online December 16, 2016